Analisis Komparasi Politik Hukum Undang-Undang Nomor 1 Tahun 2023 Dengan Kuhp Tentang Pidana Mati - Asfi, Prabangasta; Wirakusuma, Zuhana Ade (El-Dusturie, 2024)
The death penalty is placed as an alternative punishment that is imposed as an option or last resort, not the main punishment as in the old Criminal Code. Placing the death penalty as an alternative punishment in Law Number 1 of 2023 raises pros and cons in society. As a replacement for the old Criminal Code, Law Number 1 of 2023 was formed to suit the needs of the Indonesian nation. Meanwhile, the Criminal Code itself is a criminal code inherited from the Dutch colonial period which has been in effect since 1946 until now. The aim of this research is to analyze the concept of imposing the death penalty in Article 100 of Law Number 1 of 2023 with Article 10 of the Criminal Code and to understand the legal politics of imposing the death penalty in Article 100 of Law Number 1 of 2023 with Article 10 of the Criminal Code. This research uses qualitative comparative literature research by comparing the two articles to be studied with a normative research approach using secondary data sources, primary legal materials in the form of Law Number 1 of 2023 and the Criminal Code as well as secondary data sources such as books by Andi Hamzah, Soedikno, Joko Sriwidodo and R.Soesilo as well as previous research such as journals, theses and articles. The results of the research are that the concept of imposing the death penalty between Law Number 1 of 2023 and the Criminal Code has differences. Judging from the theory of language interpretation, teleological interpretation, systematic interpretation, historical interpretation and comparative interpretation, both have significant differences, but in criminal theory they both have similar principles in a combined criminal theory which aims to provide a deterrent effect and enforce the law.